Vallejo’s aesthetic adventure: The idea of beauty in the poem «Himno a los voluntarios de la República» - Prado Romero, Gustavo Marcial (2021)
The reading proposed by César Vallejo, based on his experiences during the Spanish Civil War, intercommunicated with conflicts of great dimension and wide consequences, shows the confluence of diverse perspectives relevant to Peruvian literature. This article revisits some verses of «Himno a los voluntarios de la República», from España, aparta de mí este cáliz, to approach that relevance. Literary critics affirm that César Vallejo delineated a horizon of transformation for Peruvian literature; they even consider that he established a new aesthetic proper to a new time. Thus, as a beginning point, a notion of literature in a general sense is approached; and then, this innovation of the poet is reviewed.